Comparison of medetomidine—morphine and medetomidine—methadone for sedation, isoflurane requirement and postoperative analgesia in dogs undergoing laparoscopy. (January 2017) - Raillard, Mathieu; Michaut-Castrillo, Julien; Spreux, Damien; Gauthier, Olivier; Touzot-Jourde, Gwenola; Holopherne-Doran, Delphine
Abstract: Objective: To compare the effects of intravenous (IV) medetomidine-morphine and medetomidine-methadone on preoperative sedation, isoflurane requirements and postoperative analgesia in dogs undergoing laparoscopic surgery. Study design: Randomized, crossover trial. Animals: Twelve adult Beagle dogs weighing 15.1 ± 4.1 kg. Methods: Dogs were administered medetomidine (2.5 μg kg −1 ) IV 5 minutes before either methadone (MET) or morphine (MOR) (0.3 mg kg −1 ) IV. Anaesthesia was induced with propofol, maintained with isoflurane in oxygen, and depth was clinically assessed and adjusted by an anaesthetist blinded to the treatment. Animals underwent laparoscopic abdominal biopsies. Sedation and nausea scores, pulse rate (PR), respiratory rate ( f R ), noninvasive systolic arterial blood pressure (SAP), rectal temperature (RT) and pain scores were recorded before drug administration, 5 minutes after medetomidine injection and 10 minutes after opioid administration. Propofol dose, PR, f R, SAP, oesophageal temperature (TOES ), end-tidal carbon dioxide and end-tidal isoflurane concentration(Fe ′Iso) were recorded intraoperatively. Pain scores, PR, f R, SAP and RT were recorded 10 minutes after extubation, every hour for 6 hours, then at 8, 18 and 24 hours. The experiment was repeated with the other drug 1 month later. Results: Nine dogs completed the study. After opioid administration and intraoperatively, PR, but not SAP, was significantly lower in MET.Fe ′Iso was significantly lower in MET. Temperature decreased in both treatments. Pain scores were significantly higher in MOR at 3 hours after extubation, but not at other time points. Two dogs required rescue analgesia; one with both treatments and one in MOR. Conclusion and clinical relevance: At the dose used, sedation produced by both drugs when combined with medetomidine was equivalent, while volatile anaesthetic requirements and PR perioperatively were lower with methadone. Postoperative analgesia was deemed to be adequate for laparoscopy with either protocol, although methadone provided better analgesia 3 hours after surgery.